An investigation of subjective sleep and fatigue measures for use with elite athletes - Dickinson, R. K.; Hanrahan, S. J. (Journal of Clinical Sport Psychology, 2009)
This study investigated the properties of the Athens Insomnia Scale (Soldatos et al., 2000), the Fatigue Severity Scale (Krupp et al., 1989), and subscales of the SLEEP-50 Questionnaire (Spoormaker et al., 2005) in elite Australian athletes, to determine their appropriateness for this population. Fifty-nine athletes (29 male, 30 female, M = 21.86 yrs, SD = 7.44) from elite basketball, rowing, netball, beach volleyball, and sailing squads completed measures. A subset (n = 20) completed measures again at a 1-month interval, and a further subset (n = 5) were interviewed about their thoughts regarding the measures and their understanding of sleep. All scales and subscales displayed high internal consistency, apart from that which contained items not theoretically related, and all displayed good 1-month test-retest reliability. All measures were significantly correlated, demonstrating convergent validity. Athletes reported few sleep problems, but moderate fatigue. Athletes stated the measures produced accurate reflections of their sleep and fatigue, but also suggested improvements. Research limitations and implications are discussed.